Checklist, Red List, and Distribution Pattern of Charophytes (Charophyceae, Charales) in Slovakia Based on Critical Revision of Herbarium Specimens - Alica Hindáková; Maciej Gąbka; Richard Hrivnák (Diversity, 2022)
A critical revision of charophytes collected in Slovakia from 1887 up to present, based on herbaria specimens, provided us with the opportunity to compile an updated checklist and to revaluate their threat status in order to obtain the current red list of charophytes of Slovakia. The data obtained will fill the gap in knowledge about these macroscopic algae in Central Europe. The revised list of charophytes includes 19 representatives of three genera: Chara (11), Nitella (7), and Nitellopsis (1). Following the latest IUCN red-list categories and criteria (version 3.1) and using the modified category regionally extinct (RE), derived from the category extinct (EX), 36.8% of charophytes are classified as RE (Chara connivens, C. subspinosa (=rudis), Nitella capillaris, N. confervacea, N. flexilis, N. gracilis, and N. opaca); 21% as EN (endangered; Chara braunii, Nitella mucronata, N. syncarpa, and Nitellopsis obtusa); 21% as VU (vulnerable; Chara contraria, C. gymnophylla, C. hispida, and C. virgata); 10.6% as NT (near-threatened; Chara globularis, C. vulgaris); and 5.3% as CR (critically endangered; Chara canescens) species; finally, 5.3% species could not be assessed (DD; Chara aspera).